Sound Changes in Esperanto Loanwords of English Origin - Syauqi Ahmad Zulfauzi Stya Lacksana (Passage, 2016)
This historical linguistic study aims to investigate what types of sound changes that happen in the process of linguistic borrowing from English to Esperanto and what factors triggered the changes. It is found that there are 195 English words that are borrowed according to the pronunciation, and there are four categories of sound change that is found: phonological, morphological, orthographically influenced, and abnormal sound change. Regarding the types of sound change, it is found that there are eleven sound changes: sound addition for morphological sound change (34%), vowel raising (13.1%), vowel lowering (7.7%), shortening (6.8%), monophthongization (6.2%), orthographically influenced sound change (4%), vowel raising and fronting (3.5%), fortition (2.7%), deletion (2.6%), vowel raising and backing (1.5%), and vowel lowering and backing (1.2%). It is discovered that the phonological sound changes happen to fulfill the phonological aspects of Esperanto, morphological sound changes occur due to the morphological rules of Esperanto, orthographically influenced sound changes happen to conform to the Esperanto phonological inventory and to maintain the original English spelling for easier word recognition, and abnormal sound change occur to fulfill phonological and morphological aspects of Esperanto with some influences from the orthography.Keywords: historical linguistics, sound change, loanwords, Esperanto, Esperanto studies